Small and Medium-Sized Enterprises (SMEs) Entrepreneurial Marketing in Davao City, Philippines - Rocelyn Mascarinas; Karl P. Campos (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Based on the premise that entrepreneurial marketing is appropriate for small and medium-sized businesses, the goal of this research is to investigate the entrepreneurial marketing strategy utilized by small and medium-sized enterprises in Davao City, Philippines. This is a quantitative study that relies on primary data gathered through questionnaire surveys. The sample method utilizes random sampling with 115 SMEs from Davao City, Philippines. The sample showed the highest level of adoption for Proactiveness and Innovativeness and the lowest level of adoption for Resource Leveraging, according to the results. Furthermore, that the seven Entrepreneurial Marketing aspects (proactiveness, opportunity-driven, innovativeness, risk management, resource leveraging, customer satisfaction, and value creation) were discovered to have a significant and positive correlation with business sales growth. Consequently, that the relevant Davao City authorities should hold more training sessions for SMEs on Entrepreneurial Marketing practices in order to develop a better understanding of how to grow a business.